Hazard Analysis for Phytophthora Species in Container Nurseries: Three Case Studies - Jennifer L. Parke (HortTechnology, 2019)
Phytophthora species cause crop losses and reduce the quality of greenhouse and nursery plants. Phytophthora species can also be moved long distances by the plant trade, potentially spreading diseases to new hosts and habitats. Phytosanitary approaches based on quarantines and endpoint inspections have reduced, but not eliminated, the spread of Phytophthora species from nurseries. It is therefore important for plant production facilities to identify potential sources of contamination and to take corrective measures to prevent disease. We applied a systems approach to identify sources of contamination in three container nurseries in Oregon, California, and South Carolina. Surface water sources and recaptured runoff water were contaminated with plant pathogenic species at all three nurseries, but one nursery implemented an effective disinfestation treatment for recycled irrigation water. Other sources of contamination included cull piles and compost that were incorporated into potting media, infested soil and gravel beds, used containers, and plant returns. Management recommendations include preventing contact between containers and contaminated ground, improving drainage, pasteurizing potting media ingredients, steaming used containers, and quarantine and testing of incoming plants for Phytophthora species. These case studies illustrate how recycled irrigation water can contribute to the spread of waterborne pathogens and highlight the need to implement nursery management practices to reduce disease risk.